The Role of Teachers in the Implementation of Online Learning in the midst of the Covid-19 Pandemic - Budiyanto, Agus (Prosiding University Research Colloquium, 2021)
Since the emergence of the COVID-19 Pandemic in all corners of the world, there have been changes in all fields, spreading to the education aspect. Many schools have been closed, the learning process is temporarily carried out online from their respective homes. Madrasah parties are required to continue to carry out learning with a process that is no longer face-to-face in class but with online learning. The focus of this research is to describe the teacher’s role in the implementation of online learning, from planning, implementing, and evaluating learning. This study uses a qualitative descriptive research model. This research was conducted at MI Muhammadiyah Butuh I Kalikajar with the research subjects being teachers, in this case the teachers were given questionnaires and interviews to find out several indicators of the teacher’s role, (1) the teacher’s role as a learning resource, in online learning, the teacher provides learning resources , namely the theme book and program (2) the role of the teacher as a demonstrator, in this distance learning where the teacher provides facilities such as media to assist students in the learning process; (3) the teacher’s role as a motivator, the teacher provides motivation to students. The motivation given by the teacher is also various motivations with rewards or directly to students (4) the role of the teacher as a manager, in online learning here the teacher acts as a learning manager, so that learning can be directed according to the basic competencies and learning objectives that must be achieved; (5) the role of the teacher as an evaluator here, the teacher plays a role in providing evaluations in order to find out the extent to which students master a learning material. Not only is the support for inhibiting factors very diverse, teachers play a very important role in the implementation of online learning in the midst of the Covid-19 Pandemic